Finding False Paths in Sequential Circuits; Russian Physics Journal; Vol. 60, iss. 10 - Matrosova A. Yu. Anzhela Yurjevn; Andreeva V. V. Valentina Valerjevna; Chernyshov S. V. Semen Vladimirovich; Rozhkova S. V. Svetlana Vladimirovna; Kudin D. V. Dmitry Valerjevich (2018, 2018)
Title screen